2019
DOI: 10.1111/1467-8268.12407
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Regional Economic Communities on Industrialization: The Case of COMESA

Abstract: This paper seeks to establish the contribution of the Common Market for Eastern and Southern Africa (COMESA) programmes in promoting industrialization. It further seeks to establish the link between industrialization and productivity. The paper uses a gravity model to estimate a cross-sectional time-series (panel) dataset for the period 2001-2015.The results indicate that membership to COMESA has created large markets and promoted industrialization among member states. However, results also confirm that COMESA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 28 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…With the growing international financial markets integration, there is need, now more than ever before, for evidence‐based knowledge of how markets are related and volatility shocks transmitted in the West Africa region,3 especially in light of its importance in portfolio risk management and the growing efforts to integrate regional capital markets by the West African Capital Markets Integration Council (WACMIC). Some of the benefits associated with regional capital markets integration include development of markets and institutions, effective price discovery, enhanced liquidity and capital raising, investment growth potentials and promotion of industrialisation (Akinyemi et al, 2019; Raj & Dhal, 2008; Shinyekwa et al, 2019). Conversely, volatility shock transmission and multiple contagion of systemic risk, and the resulting market instability are among the potential challenges of markets integration.…”
Section: Introductionmentioning
confidence: 99%
“…With the growing international financial markets integration, there is need, now more than ever before, for evidence‐based knowledge of how markets are related and volatility shocks transmitted in the West Africa region,3 especially in light of its importance in portfolio risk management and the growing efforts to integrate regional capital markets by the West African Capital Markets Integration Council (WACMIC). Some of the benefits associated with regional capital markets integration include development of markets and institutions, effective price discovery, enhanced liquidity and capital raising, investment growth potentials and promotion of industrialisation (Akinyemi et al, 2019; Raj & Dhal, 2008; Shinyekwa et al, 2019). Conversely, volatility shock transmission and multiple contagion of systemic risk, and the resulting market instability are among the potential challenges of markets integration.…”
Section: Introductionmentioning
confidence: 99%
“…Their research, which covered 29 countries from 2004-2014, showed that prioritizing ICT development significantly increases trade. Additionally, Shinyekwa et al (2019) examined the impact of COMESA on industrialization and productivity. Their analysis of the period from 2001-2015 confirmed the group's positive impact on industrialization, but the share of TFP was lower than expected, indicating a lack of convergence with international knowledge spillovers.…”
Section: Literature Review and Justification Of The Topicmentioning
confidence: 99%
“…The second half of the 20 th century saw a rapid increase in the literature on regional integration, which was noted by Asante (1997a, p.17) and several other scholars as a critical aspect of the development strategy, especially in developing countries and regions (AfDB, 2019;Dent & Richter, 2011;Volz, 2013). This perspective is shared by both scholars and many policymakers, and can be seen in article 70 of the treaty that established the Common Market for Eastern and Southern Africa (COMESA), which encourages member states to embrace initiatives and measures that seek to build the infrastructure and to design policies and strategies to drive industrialisation (COMESA, 1993;Shinyekwa et al, 2019).…”
Section: Continental Initiatives In the Quest For Industrialisationmentioning
confidence: 99%